Le bon usage : prévention du sida à l'adresse des usagers de drogues - Bauherz, Georges; Kaminski, Dan; Zombek, Serge (Bruxelles : Agence Prévention du Sida, 1992)
Fonds Suzan Daniel (FSD)
Frans
Monografie